Penguatan kompetensi Guru SD melalui integrasi teknologi AR dan AI dalam pembelajaran - Nisa, Choirun; Rahmawati, Fitri Puji; Kaltsum, Honest Ummi; Hidayat, Muhamad Taufik (Nur Science Institute, 2024)
Currently, AI and AR-based technologies are beginning to be used in education, but their usage in Indonesia is not yet widespread. The community service program from PGSD UMS aims to improve the understanding of partner elementary school teachers regarding AI and AR-based learning media. Through workshops in December 2023 at six partner elementary schools, namely MIM PK Wirogunan, MIM Pucangan, SDN Makamhaji 03, MIM PK Kertonatan, SDM Plus Malangjiwan, and SDIT M Al Kautsar, participants were introduced to applications such as Word Wall, Math Game Time, Quizziz, Canva, Assembler Edu, Lumio, Live Worksheet, and Filter TikTok. Each workshop was attended by around 9 to 35 participants, with a total of 100 participants. Evaluation results showed a significant improvement in participants' understanding and skills in using these applications. In addition to technical improvement, teachers' pedagogical competence also increased, as seen from the implementation of technology in daily teaching, making it more interactive and effective. Follow-up mentoring sessions in March and April 2024 helped ensure optimal application of the technology. Overall, this program successfully enhanced teachers' competencies in utilizing AI and AR technologies for better learning.